Niemiecka propaganda rewizjonistyczna w świetle „Gazety Warszawskiej” z lat 1926-1930 - Węclewska, Marta (Acta Universitatis Lodziensis. Folia Historica, 2008)
One of the most difficult problems regarding the relationship between Poland and Germany during the interwar period was the German’s revanchist propaganda which was made in the Weimar Republic. The general situation was as a result of the dissatisfaction the German nation had with the decisions of the Paris Peace Conference and the Treaty of Versailles. This was seen by Germany as both shameful and unjust, especially concerning blame for the outbreak of the First World War, Germany being disarmed and some of their provinces being given directly to Poland, amongst others. The political atmosphere in Europe in the twenties was not conducive to raising these issues. The Weimar Republic wanted to be regarded as a new democratic country. The policy of friendship with France and Great Britain did not let Germany speak aggressively about their demands. Therefore, German revanchism was turned mainly against Poland due to it being safer and not involving the western Allies. Meanwhile it was a convenient way to expressing the German people’s dissatisfaction and frustration. The Polish National Democratic Party thought that the most important subject in olish foreign policy should have been keeping to the principle of the Treaty of Versailles. The party was interested in recognising even the slightest traces of German revanchism. The Polish nationalists newspaper “The Warsaw Gazette” constantly showed examples of The Weimar Republic s propaganda. The evidence came from many different sources, in an attempt to make the Polish nation aware of how frequently revanchist demands were made in German society. The revanchist campaigning was popular not only among politicians and political parties, organizations and associations but also with scientific institutions, the press, cinema and educational establishment. Besides showing popularity of the revanchism, “The Warsaw Gazette gave countless examples of German propaganda claiming rights to these areas of, what was then, Poland. These claims included historical justification to them remaining German and questionable quality scientific papers concerning the detrimental economic and cultural consequence of loosing, what they regarded, “indigenous” territory. Naturally, besides informing its readership, “The Gazette analysed the Polish government's policy regarding anti-Polish propaganda in The Weimar Republic. The nationalist press proposed a solution which might have proved Polish rights to the disputable territories. “The Gazette” also emphasized that Poland would never agree to any territorial change. policy regarding anti-Polish propaganda in The Weimar Republic. The nationalist press proposed a solution which might have proved Polish rights to the disputable territories. “The Gazette” also emphasized that Poland would never agree to any territorial change.